A cross sectional study on reproductive health disorders in dairy cattle in Sudan - Elhassan, Amira Mohamed; Fadol, Mohamed Abdalla; Elfahal, Abdelgafar Mohamed Ali; El Hussein, Abdel Rahim Mohamed (Journal of Advanced Veterinary and Animal Research, 2015)
A cross sectional survey was carried out in dairy farms in four States of Sudan to determine prevalence of reproductive health disorders that affect dairy cattle industries in the country. A total of 575 adult female cows in dairy farms located in Khartoum, Gezira, Sennar, and White Nile States were investigated using questionnaire survey and face-to-face interviews with the owners. The results indicated that 24.4% of the animals were affected with one or more reproductive health disorders. Abortion (57.1%) represented the major health problem affecting calf yield, followed by infertility (34.3%) and neonatal death (8.6%). Other health problems included stillbirth, vaginitis and retained placenta, anomalies, metritis and repeat breeder. Most of the abortion cases were detected during third trimester (76.25%) followed by first (12.5%) and second (11.25%) trimesters. Finally, countrywide investigations of reproductive disorders and increasing awareness to the owners are recommended for designing successful control strategies of reproductive disorders in Sudan. http://dx.doi.org/10.5455/javar.2015.b57